FAO species catalogue : - Mackay, Roland J. (Food and Agriculture Organization of the United Nations, 1992)
The present volume includes comprising 31 families, 3 genera and 3 subgenera. This volume includes an introductory section with gereral remarks on habitat, biology, fisheries, systematics, zoogeography and problems of identification, a glossary of technical terms, illustrated keys to genera and species, inculding regional keys, details accounts of species, and a table of species by major fishing area.